Collaborative Filtering Recommender System pada Virtual 3D Kelas Cendekia - Angga Setia Wardana; Muhammad Idham Ananta Timur (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
Intelligent Clasrooms is a concept of modern learning process where users can perform collaborative learning wherever and whenever. With learning in Intelligent Classroom, users can get different learning experience where learning process is expected to run more effectively and efficiently. One application of the Intelligent Classrooms concept is learning by utilizing the virtual world. The information collected in the Intelligent Classroom will increase so that a system is needed. The recommendation system of collaborative filtering is the most appropriate system with the intellectual class. With the sparsity of training rate of 80%, it is implemented a collaborative filtering recommendation system with error rate which if calculated with RMSE is 1.060709 or it can be said that the accuracy level is 78.79%.